The Impact of Emotional Marketing Strategies on Brand Loyalty Among Young Adults in the Cosmetic Industry - Abass, Nada (2024)
Emotional marketing plays an essential role in shaping consumer behaviour, where brand loyalty is not only influenced by product quality but also by the emotional connections. In a competitive market, cosmetic brands utilize emotional marketing strategies to build connections with young adults by relating to their emotions and values. These strategies have become essential for developing consumer engagement and brand loyalty, as purchasing decisions are influenced by emotional factors. This thesis studies the impact of emotional marketing strategies on brand loyalty among young adults in the cosmetic industry. Emotional marketing focuses on strategies creating bonds with consumers. The research studies how these strategies influence the purchasing decisions and brand loyalty of young adults aged 18 to 25. The study begins with a literature review on emotional marketing and its significance in influencing consumer behaviour, followed by an in-depth analysis of key theoretical frameworks that support the understanding of brand loyalty. A qualitative research approach, including semi-structured interviews, was conducted to gather insights from young adults actively purchasing cosmetic products. The data were analysed using thematic analysis, revealing key themes, including the role of storytelling, influencers, and the importance of social and ethical causes in driving brand loyalty. The findings highlight that emotional marketing strategies impact young adults’ brand loyalty in the cosmetic industry. The study concludes by discussing the theoretical contributions, limitations, and future research opportunities, emphasizing the importance of emotional marketing in developing relationships between brands and consumers.